EDUCAÇÃO AMBIENTAL NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL: UMA PROPOSTA DIDÁTICO-METODOLÓGICA PARA A FORMAÇÃO DE PROFESSORES - Konflanz, Tais Lazzari (2020)
This study is part of the Teachers Qualification field of research of the Postgraduate program in Science and Mathematics Education in the Franciscan University. It has as its leading point Environmental Education (EE) in the primary education scope. EE is a contemporaneous topic that involves human life on a local, regional and global scale and must be approached in a transversal and integrative way. Inspired by this context, the purpose of this research has been to investigate how a Didactic-methodological approach in EE may contribute to primary education teachers’ qualification. The theoretical framework is supported on the methodological principles of Ecological Literacy (CAPRA, 2006) and Environmental Thinking (LEFF, 2001), complemented by the guidelines defined on the official and institutional documents. This study has a qualitative-exploratory nature, and the subjects were students of the Pedagogy course in an Undergraduate Institution in Santa Maria (Rio Grande do Sul, Brazil). The data was collected in the second semester of 2019, guided by an initial Pedagogical Intervention that aimed to get to know the subjects’ profiles better, as well as their Environmental Perceptions. Subsequently, a Didactic-methodological approach was carried out in three steps, being them: (1) Initial problematization; a survey about how EE should be addressed at schools. (2) Knowledge organization; introductory lecture on Ecological Literacy. (3) Knowledge application; two activities were carried out - a practical activity with the pitanga fruit and another one regarding the concept of tree. The interpretation of the collected data in the Pedagogical Intervention was accomplished based on the Grounded Theory as well as the EE theoretical models; the latter were also standard for the analysis of the data collected in the implemented activities of the Didactic-methodological approach. The results show that the Didactic-methodological approach implementation contributed to the qualification of the teachers-to-be in the sense that it provided new reflections and perspectives to the accomplishment of EE as a theme that has been moving and gathering strength in all educational levels and modalities, leading to the construction of a socially, politically and economically sustainable society.